Assessment of records management in National Examinations Council (NECO) branch office, Rivers State - Otu, Godwin A.; Ukubeyinje, Sandra Ejiro (Communicate: Journal of Library and Information Science, 2025)
The study examined records management practices at the National Examinations Council Office in Rivers State. Four (4) research objectives and research questions guided the study. A descriptive survey design was employed for the study. The population of the study comprised 23 staff of NECO in the Rivers State branch. A questionnaire was employed as the method of data collection. Given the relatively manageable sample, a census sampling was used. Descriptive statistics was employed in the study’s analysis of research questions, using percentages, mean and standard deviation. Findings revealed that the type of records managed at NECO include students' results, students' bio data, and examination records. For students' results, 12 respondents (63.16%) strongly agreed, and 6 respondents (31.58%) agreed. Regarding students' bio data, 10 respondents (52.63%) strongly agreed, while 7 respondents (36.84%) agreed. Lastly, for examination records, 9 respondents (47.37%) strongly agreed, and 8 respondents (42.11%) agreed. The methods employed for records preservation at NECO primarily include students' results, students' bio data, and examination records. However, the use of electronic databases, recruitment of records managers, and acidification were not common practices at NECO. Similarly, the procedures utilized for records disposition at NECO mainly involve waste management agencies, waste bins, destruction/shredding, recycling, and archiving, with digital deletion being rarely used. Despite the efforts made in records management at NECO, several challenges were encountered, including lack of records management policy, bad attitudes of staff towards record keeping, lack of skills to adopt electronic records management systems and cloud storage, corruption, lack of facilities, lack of database, and lack of record managers. The study recommended that records management be prioritized.